Genome-wide Association Study for Starch Pasting Properties in Chinese Spring Wheat - Tian, Yousheng; Sang, Wei; Liu, Pengpeng; Liu, Jindong; Xiang, Jishan; Cui, Fengjuan; Xu, Hongjun; Han, Xinnian; Nie, Yingbin; Kong, Dezhen; Li, Weihua; Mu, Peiyuan (Frontiers in Genetics, 2022)
In order to understand the genetic basis of starch pasting viscosity characteristics of spring wheat, we assessed the genetic variation of RVA parameters determined by the Rapid Visco Analyser in a panel of 192 Chinese spring wheat varieties grown in Er’shi, Shihezi and Zhaosu during 2012 and 2013 cropping seasons. A genome-wide association study with 47,362 single nucleotide polymorphism (SNP) markers was conducted to detect marker-trait associations by mixed linear model analysis. Phenotypic variations of RVA parameters ranged from 1.6 to 30.7% and broad-sense heritabilities ranged from 0.62 to 0.91. Forty-one SNP markers at 25 loci were significantly associated with seven RVA traits in at least two environments; among these, 20 SNPs were located in coding sequences (CDS) of 18 annotation genes, which can lead to discovering novel genes underpinning starch gelatinization in spring wheat. Haplotype analysis revealed one block for breakdown (BD) on chromosome 3B and two blocks for pasting temperature (T) on 7B. Cultivars with superior haplotype at these loci showed better starch pasting viscosity than the average of all cultivars surveyed. The identified loci and associated markers provide valuable sources for future functional characterization and genetic improvement of starch quality in wheat.